Conservación del nicho climático de diez especies de plantas exóticas invasoras entre sus rangos de invasión en ecuador y nativo - Zurita Bonilla, Juan Pablo (2019)
Invasive alien species live in constant adaptation to the environment and adverse environmental conditions; This is called phylogenetic conservatism of the niche, then a species introduced from any place in the world can displace another, generating environmental problems, social and economic, so the plant species selected for this Study: Aruno Donax, Cynodon nlemfuensis, Eragrostis japonica, Foeniculum vulgare, Genista Monspessulana, Momordica Charantia, Ricinus communis, Rottboellia cochinchinensis, Silene Gallica and Sonchus asper, are native species of the continents of Asia, Africa and Europe. Through the modeling of ecological niche, prediction data are obtained about the potential invasions of these species in the areas selected for the study. The objective of this research was to evaluate the conservation of the climatic niche of ten species of invasive exotic plants between their invasion ranges in Ecuador and native. It was used as a method of modeling with the logarithm of maximum entropy MaxEnt and was obtained records of presence to 1 km of the 10 species, records taken in the native area and in Ecuador; We also used the 19 bioclimatic variables of WorldClim 2.0. The binary maps were generated with the SDMTools tool from ArcGis 10.1, thanks to this we obtained geographic distribution maps in the native area and in areas of potential invasion in continental Ecuador, and the total area of potential invasion for each province, Defining the environmental conditions to which invasive alien species can be adapted the provinces of continental Ecuador with the greatest likelihood of invasion for the ten invasive alien species are Chimborazo, Azuay, Bolívar, Tungurahua and Loja, In all these areas the cold climates predominate in most of the year and to these conditions the species are adapted, therefore, the Interandina or Sierra region is the one that presents the most potential risk of invasion. The species with the greatest amount of geographic space possible of niche for invasion in Continental Ecuador was Foeniculum vulgare. The species that presented the greatest invasion potential in the Amazon region was Ricinus communis and the species with the greatest invasion potential in the coastal region was Momordica Charantia. Keywords: Phylogenetic conservatism of niche, ecological niche modeling, potential invasion area